Application of Charlson Comorbidity Index to assess prognosis of 18-month mortality in patients with acute myocardial infarction - T. H. Hoang; V. V. Maiskov; I. A. Merai; Zh. D. Kobalava (Бюллетень сибирской медицины)
Aim. To evaluate the prognostic value of the Charlson Comorbidity Index (CCI) for predicting 18-month all-cause mortality and develop a nomogram for predicting 18-month mortality in acute myocardial infarction (MI) patients. Materials and methods. The prospective, single-center, observational study included 712 consecutive patients with acute MI undergoing coronary angiography within 24 hours after hospitalization. The primary endpoint was 18-month all-cause mortality. The logistic regression analysis was adopted to identify independent prognostic factors. A nomogram for predicting the endpoint was developed using the multivariate analysis. The discriminative ability of the CCI and a nomogram were evaluated using the receiver-operating characteristic (ROC) curve analysis. Results. Of the patients, 61% were male, median age was 65 years (interquartile range (IQR) was 56–74 years). Median CCI was 4 (IQR: 3–6) points. The mortality rate was 12.1% at 18 months with the area under the curve (AUC) of 0.797 for CCI (95% confidence interval (CI) 0.746–0.849; p < 0.001). The multivariate analysis revealed that CCI (odds ratio (OR) 1.28; 95% CI 1.08–1.52; p = 0.004), age (OR 1.06; 95% CI 1.02–1.09; p = 0.002), and three-vessel coronary artery disease (OR 2.60; 95% CI 1.36–4.98; p = 0.004), incorporated into the nomogram, were independent predictive factors of an adverse outcome. The nomogram showed good discrimination in predicting 18-month mortality in patients with acute MI (AUC = 0.819; 95% CI 0.767–0.870; p < 0.001; sensitivity 65.1%; specificity 88.2%). Conclusion. CCI was independently associated with and moderately predicted 18-month mortality in patients with acute MI. The proposed nomogram facilitated early identification of high-risk patients, allowing for the implementation of more effective treatment strategies and reducing acute MI mortality